Effects of coenzyme Q10 administration on blood pressure and heart rate in adults: A systematic review and meta-analysis of randomized controlled trials - Mehdi Karimi; Samira Pirzad; Farnaz Hooshmand; Niyousha Shirsalimi; Seyed Morteza Ali Pourfaraji (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Background and objective: Coenzyme Q10 is a naturally occurring antioxidant that has been suggested to improve cardiovascular health. Studies examining the effects of Q10 on blood pressure (BP) and heart rate (HR) have found inconsistent results. This meta-analysis aims to clarify the effects of Q10 administration on BP and HR in adults. Methods: A comprehensive search of online databases was conducted until February 2025 to identify relevant randomized controlled trials (RCTs). Following screening, relevant data were extracted from the eligible studies. Statistical analyses were conducted using weighted mean differences (WMD) with 95 % confidence intervals (CI). Data analysis was performed using the ''meta'' package in R. Results: The pooled analysis of 45 RCTs (48 effect sizes) showed that Q10 administration significantly reduced systolic BP (WMD: −3.44 mmHg; 95 %CI: [-5.13 to −1.55], p < 0.01), while no significant effect was observed on diastolic BP (WMD: −1.13 mmHg; 95 %CI: [-2.16 – 0.50], p = 0.23) and HR (WMD: −0.10 bpm; 95 %CI: [-2.09 – 1.89], p = 0.44). Subgroup analysis indicated that lower doses (<200 mg/day) and longer interventions (>8 weeks) resulted in greater systolic BP reductions. Conclusion: This meta-analysis indicates that CoQ10 supplementation may be an effective adjunctive therapy for reducing systolic blood pressure, especially at doses below 200 mg/day and with longer treatment durations. However, its impact on diastolic blood pressure and heart rate appears minimal. Given its favorable safety profile, CoQ10 could be considered as a supportive option in the management of hypertension, particularly for patients seeking non-pharmacological interventions or those with mild elevations in systolic BP.